Mechanically reinforced and flame-retardant epoxy resin nanocomposite based on molecular engineering of POSS - Cheng Liu; Dongyang Zhuang; Yan Zhou; Jihua Liao; Shengping Dai; Changwang Pan; Yuntong Li; Lizong Dai; Wei Wang (Polymer Testing)
The existing flame retardants are extensively utilized for epoxy resin (EP) in the field of engineering materials with good flame retardancy. Nevertheless, their introduction often brings a substantial decrease in mechanical properties of EP. To tackle this challenge, a multifunctional nano flame-retardant (PoDOH) that is designed to enhance both the flame-retardant and mechanical properties for EP simultaneously was synthesized in this study. The results demonstrate that for EP-10 %, its hardness increased by 34.8 %, and Young's modulus increased by 25.4 %, respectively, owing to the strong interfacial interaction among EP and PoDOH derived from the ring-opening reaction. Moreover, the synergistic action of the various flame retardant elements present in PoDOH imparts excellent flame retardancy to EP-10 % (V-0 rating, LOI = 32.6 % and PHRR decreased by 48.82 %). These findings indicate that PoDOH holds great potential as a versatile and efficient flame retardant for manufacturing high-performance EP.